A Celebration of Greek Language and Culture Education in the UK. Issue 34 (15th November 2016) - Mitropoulos, Athina; Holmes-Henderson, Arlene
Abstract : On Saturday 10 June 2016, the Ambassador of the Hellenic Republic to the UK, Mr. Konstantinos Bikas, and the Classics in Communities project hosted a conference celebrating the teaching of Greek language and culture in the UK at the Hellenic Centre in London. The conference had multiple aims: to bring together a variety of teachers, committees and associations to discuss the state of Greek language and culture education in the UK; to anticipate and confront the challenges; and to collaborate to find solutions and action plans for its survival and growth.